Occupational Forecasting of Librarians in Australia - Stall, Roy. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
This paper reviews the principal sources and methods used by the Manpower Research and Information Branches of the Department of Employment and Industrial Relations (DEIR) to forecast the over or undersupply of librarians in Australia. After differentiating between manpower policy, planning, and forecasting, the role of the commonwealth government in manpower forecasting and the methodology of government-sponsored occupational research are described, with particular reference to professional librarians. It is noted that DEIR staff use data collected on their own occupational research forms supplemented by material from the Australian Bureau of Statistics (ABS), other government departments, and industry sources to compile information on: (1) workforce estimates; (2) the structure of the workforce; (3) the supply of librarians from training institutions and the percentage of graduates seeking employment; (4) current and future market demand; and (5) changes in demand. The final product of data collection and analysis is described as a prediction of the balance between expected worker supply and demand, made on the basis of a five-point scale ranging from shortage to oversupply. The conclusion to the paper notes that a minor oversupply of professional librarians is predicted in the July 1982 "Employment Prospects by Industry and Occupation," but a reduction in student intake by library schools is not recommended. (ESR)
ERIC Note: Some broken print; may not reproduce well.
Researchers.
Policymakers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Employment Projections; Foreign Countries; Government Role; Labor Needs; Labor Supply; Librarians; Library Education; Long Range Planning; National Programs; Occupational Surveys; Australia -- Manpower Research; Opinion Papers; Reports, Descriptive